Quantification of turbulent eddies in time-space and frequency domain for wave-current combined flow over side-wall roughness. (15th August 2019) - Hansda, Sunil; Barman, Krishnendu; Roy, Sayahnya; Debnath, Koustuv
Abstract: Turbulence characteristics were quantified in wave-current flow environment under the influence of the side rough walls covered with sand grain and granule roughness and comparison was made with the results for a smooth wall. The results supported the wall similarity hypothesis in the outer layer for the flow Reynolds number Re h = 31, 360 . The wall roughness cases tested here were within the transitional regime flow. Based on the roughness function or shift of the log region, the wall roughness effect on the mean velocity profile was estimated. In the wave-current flow cases for granule rough wall, most of the turbulence scales were reduced. Turbulent stresses for the rough walls increased with roughness height at the near-wall region and collapsed with the results for smooth wall in the outer region. Further, the wall normal stress was greater compared to Reynolds shear stress. The large scale eddies were observed to be distributed periodically within a broad range of frequencies at the inertial subrange regime. As a result, the energy cascading mechanisms slowed down for wave-current combined flow over rough walls. Highlights: Turbulence characteristics for sand grain and granule rough side walls. Reduction of mean velocity for waves along the flow due to less wave attenuation. In wave-current flow cases for granule rough wall, most of the turbulence scales are reduced. The energy cascading mechanisms slowed down for wave-current combined flow over rough walls.